Model Supervisi Kolaboratif Sebagai Strategi Pengembangan Profesional Guru: Studi Literatur Kritis - Fajrin, Fauziah Nur Risqi; Pratama, Raka Ilham Sapta; Khoiriah, Saidatul; Rahman, Saifullah; Dinillah, Sofyani; Rizqa, Miftahir (CV. Lentera Literasi Indonesia, 2025)
This research is a critical literature study that explores the collaborative supervision model as a strategy for teacher professional development. The study analyzes various aspects of the collaborative supervision model based on existing literature, including the concept of collaborative supervision, its impact on improving teachers' professional competence, implementation steps, and supporting arguments and criticisms of this model. The results of the analysis show that collaborative supervision has the potential to significantly improve teachers' competencies, but its implementation faces challenges such as teachers' resistance to new approaches, time constraints, and lack of training for supervisors. The study concludes that the successful implementation of this model depends on structural support and a strong collaborative culture in the school environment.